Enhancement of the resilience through microgrids formation and DG allocation with master-slave DG operation - Home-Ortiz, Juan Manuel [UNESP]; Mantovani, Jose Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The microgrids (MGs) formation is an effective alternative to provide a resilient network, however, in some cases it is not enough to recover an acceptable operational state after major faults scenarios, therefore investment actions are required. This paper presents a mixed-integer linear-programming (MILP) model for the enhancement of the resilience of distribution systems (DSs) through the optimal MGs formation with simultaneous allocation of dispatchable DG. The radial MGs are formed via reconfiguration, for this purpose, a new radiality set of constraints is proposed. On the other hand, modern DSs incorporate several DG technologies, thus, a master-slave DG operation is considered where the large existent dispatchable DGs are master units with voltage control while photovoltaic, batteries, and new allocated dispatchable DGs are slave units. Uncertainties in photovoltaic and load behavior are considered via stochastic scenario-based approach. Numerical results based on a real 135-node DS validate the effectiveness of the proposed model.
Keywords: Distribution system; Microgrids; Mixed-integer linear-programming; Planning operation; Radiality constraints; Resilience